A chionodracine-derived peptide, KHS-Cnd, as an anti-virulence agent against multidrug-resistant Acinetobacter baumannii clinical strains - Artini, Marco; Paris, Irene; Imperlini, Esther; Buonocore, Francesco; Vrenna, Gianluca; Papa, Rosanna; Selan, Laura (Frontiers in Cellular and Infection Microbiology, 2025)
About 71% of healthcare-associated infections are due to antibiotic-resistant bacteria, such as carbapenem-resistant A. baumannii, classified by World Health Organization into a critical priority group of pathogens. The antimicrobial resistance profile of A. baumannii relies on its ability to produce several virulence factors, including biofilm formation. Its ability to adhere and persist on surfaces as biofilm has contributed to its pathogenicity and drug resistance. In this study, the ability of an antimicrobial peptide (a chionodracine-derived peptide named KHS-Cnd) to inhibit or reduce biofilm formation was investigated as an example of a potential strategy to counteract infections caused by biofilm-forming pathogens. To this aim, the antimicrobial profiles were first analyzed in selected A. baumannii strains, two reference and six clinical strains, all biofilm-forming with different capability, regardless of whether they are drug resistant or sensitive. Successively, we investigated the bactericidal activity of the peptide that showed MIC values ranging from 5 to 10 µM and a significative antibiofilm activity on all tested strains at sub-inhibitory concentrations. In fact, KHS-Cnd can hinder biofilm A. baumannii strains formation with an inhibition percentage ranging between 65% and 10%. Also a statistically significant reduction of mature biofilm ranging from 20% to 50% was observed in four out of eight tested A. baumannii strains. KHS-Cnd impacts various stages of biofilm formation, including the inhibition of surface-associated and twitching motilities depending on the different strain. In particular, our results showed that only two strains possessed surface-associated motility that was strongly impaired by KHS-Cnd treatment; three clinical strains, instead, showed twitching motility, whose inhibition for two of them was evident after 24 h of incubation with peptide. Moreover, the invasion of pulmonary cells by A. baumannii was significantly impaired with a reduction of about 32% after treatment with 1.25 µM KHS-Cnd. Finally, when the peptide was used together with ceftazidime/avibactam against resistant A. baumannii strains, it was able to reduce the minimal inhibitory concentration of antibiotics needed to inhibit the microorganism growth.